SIGNIFIKANSI PENDEKATAN ALL IN ONE SYSTEM PADA KETERAMPILAN BAHASA ARAB - Nur Salam, Yufridal Fitri (Cendekia: Jurnal Kependidikan Dan Kemasyarakatan, 2011)
The approach used by teachers is one of crucial factors which can determine the success of learning process. All in one system is one of effective approaches that can be applied in teaching Arabic. This approach considers that the language is as a system consisting of functional and integrative elements representing a unity that can not be separated. Hence, the lack of one element or sub-system will cause interference and obstacles for other elements. The aforementioned language subsystem consists of pronunciation, vocabulary, grammar, and spelling. This approach suggests that language instruction should begin with teaching listening to the students, then training them to speak before facilitating them to improve their reading and writing. Thus, the sequence of teaching Arabic is listening (al-istima), speaking (al-kalam), reading (al-qiraah), and write (kitabah). In addition, it is broadly agreed that all in one system suits with the nature of brain work in looking at the phenomenon that is from the global to the parts one. Besides, it is essential that learning material and delivery techniques should be varied in order to avoid boredom that might affect the studentsâ learning. Moreover, this approach is supposed to be meaningful for the students since it focuses only on a topic or specific situation with repeated review of the various terms, as a result it can strengthen the students understanding of subject matter.ÙØ§Ù Ø§ÙÙØ¯ Ø®Ù Ø¹ÙØµØ±Ø§ ÙØ§ÙØ§ ÙÙØ¬Ø§Ø Ø§ÙÙØ¯Ø±Ø³ ÙÙ ØªØ¯Ø±ÙØ³Ù. ÙØ«ÙØ© ÙØ¯Ø§Ø®Ù ÙØ³ØªØ®Ø¯ÙÙØ§ Ø§ÙÙØ¯Ø±Ø³ ÙÙ ØªØ¯Ø±ÙØ³ Ø§ÙÙØºØ© Ø§ÙØ¹Ø±Ø¨ÙØ©Ø ÙÙÙØ§ Ø§ÙÙØ¯Ø®Ù ( all in one sistem Â ). ÙØ±Ù ÙØ°Ø§ Ø§ÙÙØ¯Ø®Ù Ø£Ù Ø§ÙÙØºØ© ÙØ¸Ø§Ù ÙØªØ±ÙØ¨ ÙÙ Ø§ÙØ¹ÙØ§ØµØ± Ø§ÙØ¯Ø§ÙØ© Ø¹ÙÙ Ø§ÙÙØØ¯Ø© Ø§ÙØªÙ ÙØ§ ÙÙÙÙ ÙØµÙÙØ§Ø ÙØ®ÙÙÙ Ø£ØØ¯ ÙÙÙØ§ ÙØØ¯Ø« Ø¹Ø§Ø¦ÙØ§ ÙÙ ØºÙØ±ÙØ§. ÙØ¹ÙØ§ØµØ± Ø§ÙÙØºØ© ÙÙ Ø§ÙØ£ØµÙØ§Øª ÙØ§ÙÙÙÙØ§Øª ÙØ§ÙØ¬ÙÙ. ÙØ§Ø¹ØªÙØ§Ø¯Ø§ Ø¹ÙÙ ÙØ°Ø§ Ø§ÙÙØ¯Ø®Ù ÙØ§Ù ØªØ¯Ø±ÙØ³ Ø§ÙÙØºØ© Ø§ÙØ¹Ø±Ø¨ÙØ© Ø¨Ø¯Ø§ÙØ© ÙÙ ØªØ¯Ø±ÙØ³ ÙÙØ§Ø±Ø© Ø§ÙØ§Ø³ØªÙØ§Ø¹ ÙÙÙØ§Ø±Ø© Ø§ÙÙÙØ§Ù ÙÙÙØ§Ø±Ø© Ø§ÙÙØ±Ø§Ø¡Ø© Ø«Ù ÙÙØ§Ø±Ø© Ø§ÙÙØªØ§Ø¨Ø©. ÙØ·Ø¨ÙØ¹Ø© ÙØ°Ø§ Ø§ÙÙØ¯Ø®Ù ÙÙØ§Ø³Ø¨Ø© Ø¨Ø·Ø¨ÙØ¹Ø© Ø§ÙØ¹ÙÙ ÙÙ ÙØ¸Ø±ØªÙ Ø¥ÙÙ Ø§ÙØ´ÙØ¡ ÙÙ Ø§ÙÙÙ Ø¥ÙÙ Ø§ÙØ¬Ø²Ø¡. ÙÙÙ Ø§ÙØªØ·Ø¨ÙÙØ ÙØ§Ù Ø§ÙØªÙÙÙØ¹ ÙÙ Ø§ÙÙØ§Ø¯Ø© Ø³ÙØ²ÙÙ Ø³Ø¢ÙØ© Ø§ÙØ·ÙØ§Ø¨. ÙØ§ÙØªØ±ÙÙØ²ÙÙ Ø§ÙÙÙØ¶ÙØ¹ Ø¨Ø´ØªÙ ÙÙØ§ØÙÙØ§ Ø³ÙÙÙÙÙ ÙÙÙ Ø§ÙØ·ÙØ§Ø¨ ÙÙØ«Ø¨ØªÙ ÙÙ Ø£Ø°ÙØ§ÙÙÙ.